1996
DOI: 10.1148/radiology.199.3.8637998
|View full text |Cite
|
Sign up to set email alerts
|

Acromial morphology: relation to sex, age, symmetry, and subacromial enthesophytes.

Abstract: Acromial shape does not vary significantly with age. It does, however, differ between sexes. The relative percentages of the types differ from previously reported values. Acromial shape tends to be symmetric. A trend between acromial type and the presence of enthesophytes is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
4
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 0 publications
7
44
4
3
Order By: Relevance
“…Type III (14%), Type I (34.6%) and Type II (51.1%) (Table II). This trend in acromial type incidence was in accordance with that reported by other authors (Edelson & Taitz, 1992;Getz et al, 1996;Nicholson et al;MacGillivray et al, 1998;Kim et al, 1999;Kane et al;Paraskevas et al;Potau et al;Saha et al, 2011;Mohamed & Abo-Sheisha, 2014) (Table II).…”
Section: Morphology Of the Acromion And Subacromial Spacesupporting
confidence: 91%
“…Type III (14%), Type I (34.6%) and Type II (51.1%) (Table II). This trend in acromial type incidence was in accordance with that reported by other authors (Edelson & Taitz, 1992;Getz et al, 1996;Nicholson et al;MacGillivray et al, 1998;Kim et al, 1999;Kane et al;Paraskevas et al;Potau et al;Saha et al, 2011;Mohamed & Abo-Sheisha, 2014) (Table II).…”
Section: Morphology Of the Acromion And Subacromial Spacesupporting
confidence: 91%
“…The results of the shape of the acromion and its different dimensions demonstrate that in the scapulae studied, the acromion type I presented in 8%, of type II in 50%, and in type III in 42%, indicating a greater presence of acromion type II in the population studied, according to studies performed by Getz et al (1996); Shah et al (2001); Natsis et al (2007); Oda et al (2000); Paraskevas et al (2008), whose investigation was carried out in macerated scapulae through visual inspection, the classification method carried out through images, also indicate a greater percentage of this type of acromion, even in those cases where authors as Shippinger et al (1997), Wang et al (2000), in their research found a greater percentage of acromion type I and II.…”
Section: Resultsmentioning
confidence: 72%
“…Çalışmaların bir kısmı kadavralar üzerin-de, bir kısmı da radyolojik görüntüler üzerinde gerçekleştirilmiştir [4][5][6] .…”
Section: Bulgularunclassified